Design and Implementation of a Web-Based RFID-Enabled Library Visitor Attendance and Management System: A Case Study at STMKG - Ahmad Meijlan Yasir; Tonny Wahyu Aji (Journal of Computation Physics and Earth Science (JoCPES), 2025)
enabled library visitor attendance and management system as a single-site case study at STMKG. Academic libraries require structured visit data to support service evaluation and institutional reporting, yet manual logbooks often produce inconsistent records and limit timely analysis. To address this issue, the proposed system digitalizes attendance capture through three integrated workflows within one platform: RFID-based identification for cadets, controlled selection for employees, and a structured manual form for public visitors. The system also provides administrative capabilities for monitoring and reporting, including visit statistics dashboards, time-filtered logs with search, and spreadsheet export for routine reporting needs. The implementation adopts a cloud-backed architecture using a modern web application frontend and a managed backend with database persistence and authentication services. Baseline security controls were incorporated to protect administrative functions and reduce automated abuse at public-facing entry points, including access verification, bot protection, and database-level access boundaries. Functional verification through end-to-end scenario testing confirms that the core attendance workflows, reporting features, and security mechanisms operate as intended within the defined scope. The resulting artifact is deployable in STMKG and can be adapted for similar higher-education libraries seeking practical visitor attendance digitalization.